Pengaruh Lokasi, Harga dan Kualitas Pelayanan Terhadap Kepuasan Konsumen di Cafe Randan UMA Kecamatan Rantepao Kabupaten Toraja Utara - Efraim Kevin; Dina Ramba; Lisa K. Wibisono (CV. Ulil Albab Corp, 2024)
This research aims to test and determine the influence of location, price and service quality on consumer satisfaction at Cafe Randan Uma, Rantepao District, North Toraja Regency. The research method uses quantitative research. The data collection technique was through a questionnaire. The population in this study were all consumers who visited Café Randan Uma and the sample used used an accidental sampling technique. The sample in this study was 43 consumers. The data analysis technique uses multiple linear regression in the SPSS 26 program. The results of this research show that, partially, the values ​​of location, price and service quality have a significant effect on consumer satisfaction at Café Randan Uma. And simultaneously Location, Price and Service Quality have a significant effect on Consumer Satisfaction at Café Randan Uma, Rantepao District, North Toraja Regency. This can be seen from the results of the F test where the significance value is 0.000 < 0.05